Acute non-lipid disseminated reticuloendotheliosis: three cases of Letterer-Siwe’s disease - Say, Burhan; Köksal, Muharrem; Sezer, Vedat (The Turkish Journal of Pediatrics, 1961)
Three cases of acute non-lipid disseminated reticuloendotheliosis are presented and the historical, clinical and pathological results are discussed.